Causes of failure of pallidal deep brain stimulation in cases with pre-operative diagnosis of isolated dystonia - Pauls, Amande; Blahak, Christian (Parkinsonism & related disorders, 2017)
Pallidal deep brain stimulation (GPi-DBS) is an effective therapy for isolated dystonia, but 10-20% of patients show improvement below 25-30%. We here…
Available online 28 June 2017
Gesehen am 22.08.2018